Rancang Bangun Aplikasi Membaca Novel Gratis Berbasis Web - Hidayat Muhammad Nur; Ulma Oktaviani (Informatics and Computer Engineering Journal, 2021)
Currently, the internet media is well received by the public, but it is not balanced with all the provisions behind it. Where the sophistication of internet technology can be used not immediately without any accompanying costs. To attract interest in Reading in this era that is not completely free, therefore it is appropriate to formulate a problem, namely to design an application as a forum for channeling a hobby that is being loved by young people, namely reading free novels. The advantages and conveniences that readers get to start from discussing the member list system, creating a homepage menu, admin, members, novel genres, novel chapters, reading history, favorites, comments, replying to comments, and searching by book titles. For the design of this novel reading application using a linear sequence model, namely the software life flow approach sequentially starting from the analysis, design, coding, testing, and support stages. The existence of this web-based free novel reading application will later provide a repertoire of choices for novel readers, as well as increase positive knowledge, especially for students. Keywords : Genre, Design, Application, Novel Reading, Free.